Frequency dependent RSSI behavior of rotating polarization waves in diverse environmental conditions - Ali, Muhammad Moazzam; Hashim, Shaiful Jahari; Ahmad, Zaid; Ferré, Guillaume; Rokhani, Fakhrul Zaman; Chaudhary, Muhammad Akmal (Institute of Electrical and Electronics Engineers Inc., 2024)
This study examines the effectiveness of Rotating Polarization Waves (RPW) in Low Power Wide Area Networks (LPWAN) under various frequencies and environmental conditions. MATLAB simulations quantified the Received Signal Strength Indicator (RSSI) across frequencies of 169 MHz, 433 MHz, 868 MHz, 915 MHz, and 2.4 GHz, and 2.4 GHz, covering distances from 10 to 10,000 meters in both rural and urban settings. The simulations incorporated transmitter power, antenna gains, system losses, and polarization mismatch loss, employing tailored path loss exponents for each scenario. The findings indicated that lower frequencies yielded enhanced coverage and a more robust RSSI, particularly in rural regions where signal propagation faced fewer obstructions. In urban environments, the received signal strength indicator showed a more pronounced decrease with distance, influenced by barriers such as buildings. Graphical representations of RSSI versus distance and frequency illustrated the variations in propagation, affirming that lower frequencies exhibit superior performance in both environments. The findings provide important insights for enhancing LPWAN deployment, highlighting the significance of frequency selection and environmental factors to achieve better coverage and reliability.